Assembly of Francisella novicida Cpf1 endonuclease in complex with guide RNA and target DNA. Issue 7 (1st July 2017) - Alcón, Pablo; Montoya, Guillermo; Stella, Stefano
Abstract : The purification, reconstitution and crystallization of a complex of F. novicida Cpf1 with CRISPR RNA and target DNA is described. Abstract : Bacteria and archaea use the CRISPR–Cas system as an adaptive response against infection by foreign nucleic acids. Owing to its remarkable flexibility, this mechanism has been harnessed and adopted as a powerful tool for genome editing. The CRISPR–Cas system includes two classes that are subdivided into six types and 19 subtypes according to conservation of the cas gene and loci organization. Recently, a new protein with endonuclease activity belonging to class 2 type V has been identified. This endonuclease, termed Cpf1, in complex with a single CRISPR RNA (crRNA) is able to recognize and cleave a target DNA preceded by a 5′‐TTN‐3′ protospacer‐adjacent motif (PAM) complementary to the RNA guide. To obtain structural insight into the inner workings of Cpf1, the crystallization of an active complex containing the full extent of the crRNA and a 31‐nucleotide dsDNA target was attempted. The gene encoding Cpf1 from Francisella novicida was cloned, overexpressed and purified. The crRNA was transcribed and purified in vitro . Finally, the ternary FnCpf1–crRNA–DNA complex was assembled and purified by preparative electrophoresis before crystallization. Crystals belonging to space group C 2221, with unit‐cell parameters a = 85.2, b = 137.6, c = 320.5 Å, were obtained and subjected to preliminary diffraction experiments.